Circulating platelets supply ST6Gal-1 in patients with IgA nephropathy. Issue 2 (17th February 2023) - Liu, Youxia; Chen, Hongshan; Li, Hongfen; Wang, Fanghao; Jia, Junya; Yan, Tiekun
ABSTRACT: Background: Our previous study showed ST6 β-galactoside α2, 6-sialyltransferase 1 (ST6Gal-1) levels in plasma were associated with a slower progression of IgA nephropathy (IgAN). Platelets are the crucial regulator of cell surface glycosylation events in circulation by supplying glycosyltransferases. Methods: A total of 180 patients with IgAN were included in this study. ST6Gal-1 levels were analyzed before and after activation of platelets by flow cytometry. Results: We found that IgAN patients in the higher platelet counts group exhibited higher levels of ST6Gal-1 compared with the lower platelet counts group. There was a positive correlation between platelet counts and ST6Gal-1 levels in plasma. Patients with higher platelet counts had higher levels of IgA, serum C3, serum C4 and proteinuria, higher percentages of platelet crits, S1 and T1/2, lower levels of platelet distribution width and the mean platelet volume, as well as a lower percentage of platelet large cell ratio compared with those patients with lower platelet counts. No differences were found in terms of the eGFR decline and composite kidney endpoints between two groups. Furthermore, we investigated whether platelets were activated and released ST6Gal-1 in patients with IgAN. The expression of CD62P in platelets in patients with IgAN was higher than those of healthy controls. There were no obvious changes in ST6Gal-1 levels between the rest and the activated platelets within 1 to 2-hour, however, the difference in ST6Gal-1 levels became more pronounced after 4-hour of incubation. Conclusions: In conclusion, human circulating platelets contain ST6Gal-1, which may be released by the activation of platelets in IgAN. Plain Language Summary: What is the context? Our previous study showed ST6 β-galactoside α2, 6-sialyltransferase 1 (ST6Gal-1) levels in plasma were associated with a slower progression of IgA nephropathy (IgAN). Platelets are the crucial regulator of cell surface glycosylation events in circulation by supplying glycosyltransferases. Whether elevated ST6Gal-1 in plasma is partly from platelets in IgAN has not been fully elucidated. What is new? A total of 180 patients with IgAN were included in this study. We found that IgAN patients in the higher platelet counts group exhibited higher levels of ST6Gal-1 compared with the lower platelet counts group. Patients with higher platelet counts had higher levels of IgA, serum C3, serum C4 and proteinuria, higher percentages of platelet crits, S1 and T1/2, lower levels of platelet distribution width and the mean platelet volume, as well as a lower percentage of platelet large cell ratio. There were no differences in terms of the eGFR decline and composite kidney endpoints between two groups. Furthermore, we explored whether platelets were activated and released ST6Gal-1 in patients with IgAN. The expression of CD62P in platelets in patients with IgAN was higher than that of healthy controls. There were no obvious changes in ST6Gal-1 levels between the rest and the activated platelets within 1 to 2-hour, however, the difference in ST6Gal-1 levels became more pronounced after 4-hour of incubation. What is the impact? Human circulating platelets contain ST6Gal-1, which can be released upon platelets activation. These findings suggest ST6Gal-1 is dynamically controlled by platelet activation to remodel cell surface glycans and alter cell behavior.